Weakly nonlinear Fredholm integrodifferential equations with degenerate kernel in Banach spaces - Zhuravliov, V.; Fomin, M. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.968.2 We consider weakly nonlinear Fredholm integrodifferential equations with degenerate kernel in Banach spaces. Necessary conditions are established for the existence of a solution, which turns into the generating solution for ε = 0. We also obtain sufficient conditions for the existence of at least one solution and construct a convergent iterative algorithm for its determination.